Life under pressure : mortality and living standards in Europe and Asia, 1700-1900 - Bengtsson, Tommy (MIT Press Eurasian population and family history series., 2004)
A pioneering work in comparative history and social science that compares population behavior in response to adversity in Europe and Asia. This highly original book--the first in a series analyzing historical population behavior in Europe and Asia--pioneers a new approach to the comparative analysis of societies in the past. Using techniques of event history analysis, the authors examine 100,000 life histories in 100 rural communities in Western Europe and Asia to analyze the demographic response to social and economic pressures. In doing so they challenge the accepted Eurocentric Malthusian view of population processes and demonstrate that population behavior has not been as uniform as previously thought--that it has often been determined by human agency, particularly social structure and cultural practice. The authors examine the complex relationship between human behavior and social and economic environment, analyzing age, gender, family, kinship, social class and social organization, climate, food prices, and real wages to compare mortality responses to adversity. Their research at the individual, household, and community levels challenges the previously accepted characterizations of social and economic behavior in Europe and Asia in the past. The originality of the analysis as well as the geographic breadth and historical depth of the data make Life Under Pressure a significant advance in the field of historical demography. Its findings will be of interest to scholars in economics, environmental studies, demography, history, and sociology as well as the general reader interested in these subjects.